Influence of Planting Date on Growth, Yield, Proximate and Mineral Compositions of Groundnut (Samnut 24) - Olalekan Oluwaseun ABE; Akindeyi Luwoye; Bolaji Umar Olayinka; Abdulaziz Ayinla (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Understanding the optimal planting date is essential to maximize agricultural productivity and ensure nutritional quality. This study aimed to analyze the effect of different planting dates on the growth, yield, proximate composition, and mineral composition of selected peanuts (Samnut 24). This study was an experimental field study. The subjects of this study were peanut plants of SAMNUT 24. Yield and yield components, such as number of pods, seeds, seed weight, pod weight, and total yield, were recorded at harvest. Proximate analysis was conducted to determine the content of water, protein, fat, fiber, ash, and carbohydrates, while mineral analysis focused on essential nutrients such as potassium, magnesium, and iron. The findings showed that planting date significantly affected the growth, yield, proximate composition, and mineral content of peanuts (Samnut 24), with advantages for early planting. Early planting during the growing season increases plant height, number of leaves, and leaf area index of peanuts (Samnut 24). In addition, early planting was the optimal planting date for the number of pods, seeds per plant, increase in pod weight, seed weight, and increase in pod and seed yield. Early planting ensures that groundnuts get the required thermal time to optimize yield components and harvest, thus ensuring better productivity and yield efficiency. The optimal planting date is early planting because much higher moisture, fiber, protein, and ash values are obtained from early planted groundnuts.